Exploring the Dynamics of Teacher-Student Relationships in Vietnamese Higher Education: A Qualitative Study of EFL Teachers’ Relational Tools - Pham, Trut Thuy; Le, Thanh Thao (Jurnal Komunikasi Pendidikan, 2025)
This qualitative study investigates the relational tools used by Vietnamese EFL teachers in higher education, a critical yet underexplored aspect in the field of language education. Focusing on the perspectives of nine Vietnamese EFL teachers from two institutions, representing various career stages (novice, mid-career, and near-end), this research provides in-depth insights into the strategies employed to build and maintain effective teacher-student relationships. Employing semi-structured interviews, the study revealed three key themes: building rapport through personalized learning, nurturing a supportive classroom environment, and emphasis on empathy and understanding. These themes highlight the importance of tailoring teaching to individual student needs, creating inclusive and supportive classroom atmospheres, and employing empathy in understanding student challenges. The findings underscore the role of relational pedagogy and sociocultural theory in enhancing the effectiveness of EFL teaching and learning. The study also sheds light on the unique context of Vietnamese higher education, where cultural nuances play a significant role in the dynamics of language education. This study contributes to the broader discourse on EFL teaching methodologies, emphasizing the critical role of teacher-student relationships in successful language acquisition.